#TITLE_ALTERNATIVE# - SETIAWAN (NIM 12007061), AFRIZON
Study area is located at Kamal village and surrounding area, , Brebes District, Central Java, with the total area of Ã‚Â±17.5 km2. This study aim to know about geological feature and correlate it to land use aspect in study area. The methods are geological mapping and geology processing data, including primary and secondary data. Stratigraphic unit in the study area is divided into four lithostratigraphy units which are, from oldest to youngest, are Limestone-Claystone Unit, Sandstone- Claystone Unit, Claystone Unit, and Aluvial Deposit Unit. Structural geology developed in the study area are reserve fault, strike slip fault, and fold. Geomorphological Analysis including river flow pattern analysis, contour pattern, slope analysis, and field observation divides study area reveal four geomorphologic units. Those are Pasir Pamipiran Homoclinal Ridge, Leuweungkolot Anticlinal Ridge, Pamulihan Folding Valley, and Aluvial unit. All analysis shows correlation with geologic condition that study area is in mature geomorphic stage. Land use map of the study area is derived using Analytical Hierarchy Process (AHP) and Geographical Information System (GIS). Five parameters such as slope map, lithology, geomorphology, land wetness, and vegetation density are used in the analysis. As the result, there are four categories of land for evaluation purpose in land farm using in study area, which are Very good zone , good zone, poor zone, and very poor zone.